Nano-bio finishing of cotton fabric with chitosan nano-hydrogels containing Rhus coriaria (L). Issue 11 (June 2021) - Taghavi, Loza; hemmatinegad, Nahid; Bashari, Azadeh; Noorian Najafabadi, Seyyed Abbas; Shakibi, Sepideh
The goal of this paper was to study some chemical and physical effects of chitosan nano-hydrogels containing Rhus coriaria on cotton fabric. The finished fabrics showed antimicrobial effects against two pathogenic microorganisms, namely Staphylococcus aureus and Escherichia coli, and the particle size, as well as the effect of encapsulating sumac extract in chitosan nano-hydrogel on some physical and visual characteristics of fabrics, are then confirmed by using various methods, including antimicrobial testing, scanning electron microscopy, Fourier transform infrared spectroscopy and ultraviolet-visible spectroscopy. The encapsulation efficiency and release behavior of the samples are also studied. The as-prepared samples with higher sumac content have more ultraviolet (UV) absorbing activity (about 52%) than the un-treated sample, as well as excellent washing fastness and antimicrobial properties after five washing cycles. More specifically, these methods indicated negligible changes in color and thickness of treated cotton fabrics. Finally, the application of cotton fabric along with the synthesis of chitosan nano-hydrogel and sumac loading introduced a novel cotton fabric with high antimicrobial properties, washing fastness and UV protection property.